The impact of heterogeneity of the air-blood barrier on control of lung extravascular water and alveolar gas exchange - Miserocchi, Giuseppe (Frontiers in Network Physiology, 2023)
The architecture of the air-blood barrier is effective in optimizing the gas exchange as long as the air-blood barrier maintains its specific feature of extreme thinnes to favour gas exchange. This feature reflects a strict control on extravascular water that is kept at minimum. Despite the existence of morphological and mechanical heterogeneities of the terminal lung units, the efficiency of the oxygen diffusion-transport function at the level of the air-blood barrier is assured in physiological conditions. Efficiency becomes critical in edemagenic conditions that notably cause an increase in microvascular filtration causing tissue swelling at the level of the air-blood barrier. This characteristically occurs when cardiac output increases to balance the oxygen uptake with the oxygen requirement such as in exercise and hypoxia exposure (either due to low ambient pressure or reflecting a pathological condition). This review, merging data from experimental approaches and evidence in humans, will explore how the heterogeneity in the morphology and perfusion of the terminal respiratory units come into play to impact on lung fluid balance and in turn on the efficiency of the oxygen diffusion-transport at the level of the alveolar-capillary unit. Further, evidence is provided concerning inter-individual differences in humans justifying the proneness to develop lung edema.